The Security Dimensions of Religious Life in Ukraine: A Focus On Orthodoxy in the Cross-Border Chernivtsi Region - Горохолінська, Ірина; Бродецький, Олександр (My University, 2023)
The article analyzes the modern tendencies in the religious space of Ukraine with a focus on the processes that are taking place in Orthodoxy in the context of transformations in the self-identification of the faithful. Changes in the jurisdictional affiliation of the Orthodox communities in Ukraine are taken into account. The dynamics of these processes are analyzed against the background of the full-scale war that Russia has unleashed and is waging against Ukraine. Special attention is paid to the situation in Chernivtsi border region, in particular, from the point of view of the Ukrainian-Romanian geopolitical and church relationships. A number of recent statements of religious leaders and decisions of church authorities are analyzed, and their social and moral role is interpreted. The text and conclusions correlate church-religious episodes in Ukraine and in Chernivtsi region with the most important security needs of Ukraine, which is the need to liberate the Ukrainian territories from the Russian occupiers and achieve victory and peace.
Keywords: religious life; security; Orthodoxy; social religion functionality; values; religious leaders; релігійні лідери / лідерство; цінності; соціальна функціональність релігії; Православ'я; безпека; релігійне життя